2023
DOI: 10.3390/ijerph20042934
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of the Factors Influencing Hearing Protection Device Usage among Industrial Workers

Abstract: This systematic literature review (SLR) aims to determine the factors influencing the use of hearing protection devices (HPDs) among industrial workers. This study was guided by the PRISMA Statement (Preferred Reporting Items for Systematic reviews and Meta-Analyses) review method, and four databases comprising Scopus, Science Direct, PubMed, Wiley Online Library, and Google Scholar were employed. A total of 196 articles were identified, and 28 studies on the factors associated with HPD use among industrial wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…The latest review [ 11 ] showed that the five main factors affecting HPD wearing by workers are sociodemographics, context, interpersonal relationships, cognitive perceptions, and health-promoting behaviors. Taban [ 12 ] and Meira [ 13 ] et al pointed out that workers’ age, education, gender, economic level, etc., were significantly related to the use of HPDs.…”
Section: Introductionmentioning
confidence: 99%
“…The latest review [ 11 ] showed that the five main factors affecting HPD wearing by workers are sociodemographics, context, interpersonal relationships, cognitive perceptions, and health-promoting behaviors. Taban [ 12 ] and Meira [ 13 ] et al pointed out that workers’ age, education, gender, economic level, etc., were significantly related to the use of HPDs.…”
Section: Introductionmentioning
confidence: 99%